Development of the automatic system for switching on the generating equipment for parallel operation with the electric power system - V. A. Fyodorova; V. F. Kirichenko; G. V. Glazyrin (Известия высших учебных заведений: Проблемы энергетики)
RELEVANCE. Synchronization is an algorithm of actions to switch on synchronous generators for parallel operation with the power system and is an integral part of the power generation process. In practice, the process of synchronization involves some difficulties. The developed automatic synchronization device is digital and is integrated into the microprocessor terminal of the CPA-M complex, allowing to solve the arising problems by means of synchronization using different methods, including the developed method of accelerated synchronization.THE PURPOSE. Create a comprehensive automated synchronization system based on the CPA-M microprocessor terminal (manufactured by a Novosibirsk company) with a variability of methods. Analyze existing synchronization devices, synthesize traditional synchronization methods, create a non-traditional intermediate method on their basis and integrate it into the automated system. Develop algorithms for the measuring and logical units, as well as for the synchronization system output unit. Experimental testing of algorithms by feeding real signals from voltage sensors on a physical model with a rotating synchronous machine (12 kW generator under test).METHODS. The problem of research studied using theoretical and practical approaches. Theoretical methods - analysis, synthesis and classification. Practical methods - modeling in MatLab® environment, comparison, experiment, observation.RESULTS. The paper describes the architecture, construction principles, settings selection of the synchronization system, as well as the interaction of its logical part with adjacent units (measuring unit, output unit). The work gives a comprehensive description of the system setup and integration of its measuring and logic parts into the CPA-M microprocessor terminal with a test on a physical object.CONCLUSION. The system has extended functionality compared to analogs, allowing the use of traditional methods and the developed method of accelerated synchronization. The results predict reduction of capital costs for automation systems, as one device provides synchronization on several circuit breakers and reduction of generator operation costs, as using this system, machine parts exposed to unacceptable thermal and mechanical effects. The development is relevant for the elimination of emergencies in the power system and reducing thermal and dynamic impacts on the generator. The social importance of the project is the exclusion of the human factor. The prospect of using the development - in the educational process of the university and at real power facilities, in particular on large synchronous generators.